Overview of the state of the art of constructed wetlands for decentralized wastewater management in Brazil. (1st February 2017) - Machado, A.I.; Beretta, M.; Fragoso, R.; Duarte, E.
Abstract: Conventional wastewater treatment plants (WWTPs) commonly require large capital investments as well as operation and maintenance costs. Constructed wetlands (CWs) appear as a cost-effective treatment, since they can remove a broad range of contaminants by a combination of physical, chemical and biological processes with a low cost. Therefore, CWs can be successfully applied for decentralized wastewater treatment in regions with low population density and/or with large land availability as Brazil. The present work provides a review of thirty nine studies developed on CWs implemented in Brazil to remove wastewater contaminants. Brazil current sanitation data is also considered to evaluate the potential role of CWs as decentralized wastewater treatment. Performance of CWs was evaluated according to (i) type of wetland system, (ii) different support matrix (iii) vegetation species and (iv) removal efficiency of chemical oxygen demand (COD), biological oxygen demand (BOD5 ), nitrogen (N), and phosphorus (P). The reviewed CWs in overall presented good efficiencies, whereas H-CWs achieved the highest removals for P, while the higher results for N were attained on VF-CW and for COD and BOD5 on HF-CW. Therefore, was concluded that CWs are an interesting solution for decentralized wastewater treatment in Brazil since it has warm temperatures, extensive radiation hours and available land. Additionally, the low percentage of population with access to the sewage network in the North and Northeast regions makes these systems especially suitable. Hence, the further implementation of CW is encouraged by the authors in regions with similar characteristics as Brazil. Highlights: The state-of-art of Brazilian sanitation is presented. The application of CWs systems in Brazil is reviewed. Treatment performance of various types of CWs is assessed. Brazilian native macrophytes species are identified. The effect of CWs design on removal efficiencies is examined.